2017
DOI: 10.1038/s41398-017-0048-8
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated epigenetic aging and mitochondrial DNA copy number in bipolar disorder

Abstract: Bipolar disorder (BD) has been previously associated with accelerated aging; yet, the mechanisms underlying this association are largely unknown. The epigenetic clock has been increasingly recognized as a valuable aging marker, although its association with other biological clocks in BD patients and high-risk subjects, such as telomere length and mitochondrial DNA (mtDNA) copy number, has never been investigated. We included 22 patients with BD I, 16 siblings of BD patients, and 20 healthy controls in this ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 74 publications
7
91
4
Order By: Relevance
“…The difference between (predicted) DNAm and chronological age (Δage) is associated with a wide-range of health and disease outcomes. For example, DNAm age acceleration in blood is associated with all-cause mortality [15][16][17][18] , socioeconomic adversity and smoking 19 , metabolic outcomes, such as body mass index and obesity 20,21 , and brain-related phenotypes, such as Parkinson's disease, posttraumatic stress disorder, insomnia, major depressive disorder, and bipolar disorder [22][23][24]25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…The difference between (predicted) DNAm and chronological age (Δage) is associated with a wide-range of health and disease outcomes. For example, DNAm age acceleration in blood is associated with all-cause mortality [15][16][17][18] , socioeconomic adversity and smoking 19 , metabolic outcomes, such as body mass index and obesity 20,21 , and brain-related phenotypes, such as Parkinson's disease, posttraumatic stress disorder, insomnia, major depressive disorder, and bipolar disorder [22][23][24]25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Even in FTD cases with underlying monogenic causes, patients manifest symptoms only later in life (Chare et al, 2014). Biological evidence supports the theory of accelerating aging in BD (Fries et al, 2017;Vasconcelos-Moreno et al, 2017). This evidence includes the association between accelerated epigenetic aging and lower global functioning in BD patients (Fries et al, 2017).…”
Section: Hypothetical Model Of Molecular Mechanisms Shared By Bipolarmentioning
confidence: 63%
“…Recently, Fries et al 17 demonstrated that it is possible to identify an acceleration of the epigenetic clock in individuals with BD compared to healthy controls. This epigenetic aging can be estimated by studying the methylation of different regions of DNA, which are known to change with age (DNA methylation age), and by the mitochondrial DNA copy number.…”
Section: Editorialmentioning
confidence: 99%
“…In that study, older patients with BD presented premature epigenetic aging compared to healthy controls, suggesting that epigenetic changes could be mechanistically linked to psychopathology in BD. 17 Another biological dimension of aging that seems to be altered in BD is the immune system aging. Several reports are available on the association between manic and depressive episodes and proinflammatory states, 18,19 Bipolar disorder (BD) is a chronic and recurrent and increased proportions of senescent T cells.…”
Section: Editorialmentioning
confidence: 99%